Spatial attention can bias search in visual short-term memory - Nobre, Anna C.; Griffin, Ivan C.; Rao, Anling (Frontiers in Human Neuroscience, 2008)
Whereas top-down attentional control is known to bias perceptual functions at many levels of stimulus analysis, its possible influence over memory-related functions remains uncharted. Our experiment combined behavioral measures and event-related potentials (ERPs) to test the ability of spatial orienting to bias functions associated with visual short-term memory (VSTM), and to shed light on the neural mechanisms involved. In particular, we investigated whether orienting attention to a spatial location within an array maintained in VSTM could facilitate the search for a specific remembered item. Participants viewed arrays of one, two or four differently colored items, followed by an informative spatial (100% valid) or uninformative neutral retro-cue (1500–2500 ms after the array), and later by a probe stimulus (500–1000 ms after the retro-cue). The task was to decide whether the probe stimulus had been present in the array. Behavioral results showed that spatial retro-cues improved both accuracy and response times for making decisions about the presence of the probe item in VSTM, and significantly attenuated performance decrements caused by increasing VSTM load. We also identified a novel ERP component (N3RS) specifically associated with searching for an item within VSTM. Paralleling the behavioral results, the amplitude and duration of the N3RS systematically increased with VSTM load in neutral retro-cue trials. When spatial retro-cues were provided, this “retro-search” component was absent. Our findings clearly show that the infl uence of top-down attentional biases extends to mnemonic functions, and, specifically, that searching for items within VSTM can be under flexible voluntary control.